A Rail Capacity Framework: Making The Case For Rail Freight Evaluation in Indonesia - Woroniuk, Clare; Aditjandra, Paulus (CSID Journal of Infrastructure Development, 2015)
Rail is being promoted to play an increasing role in reducing the external cost of freight transportation globally. This is especially the case for nations with high economic growth, such as Indonesia, which require a reliable and efficient transportation system to support global logistics. Ironically, rail freight services in Indonesia have been in decline for more than a decade due to a number of factors including the prioritization of passenger services and strong competition from the road sector. This paper aims to provide a platform for empirical research contextualizing a rail capacity framework, to be applied to the Indonesian system, with a focus on freight services. A desktop review of methodologies employed for capacity evaluation was carried out, in order to identify the most suitable approach for Indonesia. The application of these methodologies will assist in determining current capacity – utilized and unutilized – the results from which can be exercised in future strategic planning.